DNA-barcoding as molecular marker for seafood forensics: Species identification of locally consumed shark fish products in the world's largest shark fishery. (May 2019) - Muttaqin, E; Abdullah, A; Nurilmala, M; Ichsan, M; Simeone, B M; Yulianto, I; Booth, H
Abstract: Indonesia is the heart of the Coral Triangle–the global epicenter for marine biodiversity, and home to many endemic, threatened and protected species. There is a need for rapid, low-cost methods to better identify and tackle seafood fraud in Indonesia because Indonesia is also the world's largest shark fishing nation. Levels of domestic consumption of sharks and their relatives are thought to be significant, with different drivers of consumption across different products and geographies, including active and passive consumption, where passive consumers being unaware of the species origin of their seafoods. This study applies a COI DNA barcoding method to identify seafood products sold in local markets, with the aim of better understanding of the species composition about non-fin shark products in the domestic trade, and assessing the reliability of the COI method for seafood forensics. The results showed that all sampled seafood products were successfully identified to the species level, with an accuracy of 97-100%. Samples varied from different products including satay, salted meat, and meat curry, which are mostly sold in traditional markets. The magnitude, distribution and drivers of domestic consumption of shark product need to be understood in order to guide the design of future conservation.